Contemplating Dichotomous Nature of Gamma Delta T Cells for Immunotherapy - Bhat, Jaydeep; Placek, Katarzyna; Faissner, Simon (Frontiers in Immunology, 2022)
γδ T cells are unconventional T cells, distinguished from αβ T cells in a number of functional properties. Being small in number compared to αβ T cells, γδ T cells have surprised us with their pleiotropic roles in various diseases. γδ T cells are ambiguous in nature as they can produce a number of cytokines depending on the (micro) environmental cues and engage different immune response mechanisms, mainly due to their epigenetic plasticity. Depending on the disease condition, γδ T cells contribute to beneficial or detrimental response. In this review, we thus discuss the dichotomous nature of γδ T cells in cancer, neuroimmunology and infectious diseases. We shed light on the importance of equal consideration for systems immunology and personalized approaches, as exemplified by changes in metabolic requirements. While providing the status of immunotherapy, we will assess the metabolic (and other) considerations for better outcome of γδ T cell-based treatments.